A adição do fator de risco momento ao modelo dos três fatores de Fama & French, aplicado ao mercado acionário brasileiro - Mussa, Adriano (2007)
The purpose of this dissertation is to test the four-factor pricing model on the Brazilian stock market. This model is the Fama & French´s tree-factor pricing model augmented by a momentum factor. So, the four factors are: the market, as defined by the CAPM; the firm size, defined by the market value of equity; the book-to-market ratio, the relation between a company s book and market value of equity; and the momentum, defined by the stocks past return. The employed test methodology was the same used by Fama & French (1993). The database was composed by all stocks listed on the Bolsa de Valores de São Paulo BOVESPA, from 1995 to 2007. The significance of the model and of each factor was tested observing the adjusted determination coefficient, Adj. R2, of the temporal regressions and the t-Student statistics. The results indicated that the four-factor pricing model is valid for use on the Brazilian stock market, and is superior to the tree-factor pricing model and to the CAPM. The importance of each factor changes according to the portfolio characteristics.